Foundations of Hardware IP Protection - Bossuet, Lilian; Torres, Lionel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive and up-to-date guide to the design of security-hardened, hardware intellectual property (IP). Readers will learn how IP can be threatened, as well as protected, by using means such as hardware obfuscation/camouflaging, watermarking, fingerprinting (PUF), functional locking, remote activation, hidden transmission of data, hardware Trojan detection, protection against hardware Trojan, use of secure element, ultra-lightweight cryptography, and digital rights management. This book serves as a single-source reference to design space exploration of hardware security and IP protection. · Provides readers with a comprehensive overview of hardware intellectual property (IP) security, describing threat models and presenting means of protection, from integrated circuit layout to digital rights management of IP; · Enables readers to transpose techniques fundamental to digital rights management (DRM) to the realm of hardware IP security; · Introduce designers to the concept of salutary hardware, difficult to circumvent embedded hardware security systems.
Digital Right Management for IP Protection -- Turning Electronic Circuits Features into On-Chip Locks -- Logic Modification-Based IP Protection Methods: An Overview and a Proposal -- IP FSM Watermarking -- Side Channel Analysis, an Efficient Ally for IP Protection -- Hardware Obfuscation -- An application of Partial Hardware Reverse Engineering for the Detection of Hardware Trojan -- Linear Complementary Codes: Novel Hardware Trojan Prevention and Detection Approach -- Ultra-Lightweight Implementation in Area of Block Ciphers -- Enhancing Secure Elements - Technology and Architecture.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation